1998
DOI: 10.1007/s101200050054
|View full text |Cite
|
Sign up to set email alerts
|

Early gastric cancer: Report of 58 cases

Abstract: Abstract:Background. This retrospective study was carried out to review our surgical experience and to define the clinicopathologic profile of early gastric cancer in a Western country with one of the highest incidences in the world. Methods. Fifty-eight patients who had gastric surgery for early gastric cancer were included in this study. Results. The incidence of early gastric cancer was 13.9% of the patients with resected gastric cancer (58/416). The mean age of these 58 patients at diagnosis was 56.8 ؎ 12.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
1
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 29 publications
3
50
1
2
Order By: Relevance
“…Pathological findings were quite similar to those of previously published reports with regard to depth of infiltration, lymph node involvement, or histological differentiation [6,8,19,20].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Pathological findings were quite similar to those of previously published reports with regard to depth of infiltration, lymph node involvement, or histological differentiation [6,8,19,20].…”
Section: Discussionsupporting
confidence: 89%
“…The duration of symptoms before diagnosis tended to be longer than in advanced carcinoma [19]. A previous history of peptic ulcer is not uncommon (44% in our series).…”
Section: Discussioncontrasting
confidence: 48%
“…Many authors have reported that, in some patients, there are N2 lymph node metastases of gastric carcinoma which invade to the submucosal layer [13][14][15][16][17]. Survival rate.…”
Section: Resultsmentioning
confidence: 99%
“…It is generally accepted that surgical resection is the most powerful tool for improving the prognosis when early diagnosis of gastric cancer is successful (33). Unfortunately, most gastric cancers are diagnosed late at a locally advanced stage.…”
Section: Discussionmentioning
confidence: 99%